(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Folic acid, when administered periconceptionally, is now well recognized as having the potential to prevent a variety of neural tube disorders. Folic acid seems not to treat a nutritional deficiency in pregnant women, according to a recent research. Rather, it seems that these neural tube anomalies are caused by a metabolic flaw or errors, which may be corrected with enough folic acid. Folic acid seems to have the most influence on homocysteine metabolism, according to a new research. We observed that moms who were carrying diseased fetuses had much greater homocysteine levels than those who were not. These data suggest that one of the enzymes involved in homocysteine metabolism is likely to be aberrant in afflicted pregnancies. The conversion of homocysteine to methionine may be the essential stage, according to animal research. In cultured rat embryos, methionine is necessary for neural tube closure. Homocysteine metabolism necessitates the enzymes methionine synthase, cystathionine synthase, and 5, 10 methylene tetrahydrofolate reductase. If methionine synthase is the dominant enzyme, vitamin B-12, such as folic acid, has a higher chance of activating the aberrant enzyme, posing a public health risk. Vitamin B-12 may find things simpler to limit the amount of folic acid in fortified foods, reducing the risk of folic acid overdose.